2007
DOI: 10.1016/j.jcat.2006.10.028
|View full text |Cite
|
Sign up to set email alerts
|

A three-site Langmuir adsorption model to elucidate the temperature, pressure, and support dependence of the hydrogen coverage on supported Pt particles

Abstract: The three-site adsorption model, previously developed to describe H adsorption on small Pt particles, was used to gain insight into dependence of hydrogen coverage on temperature, pressure, and support ionicity. The three sites, in order of decreasing Pt-H bond strength, involve H in an atop, a threefold, and an ontop Pt site. The ontop site designates H bonded in an atop site surrounded by occupied threefold sites (hence referred to as ontop site). The model includes an emptying of the H atop sites into H thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
(63 reference statements)
6
25
0
1
Order By: Relevance
“…Sites shaded in grey represent filling of the corner/edge sites and those in red the face sites. Adapted from Ji et al . copyright 2007 with permission from Elsevier.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Sites shaded in grey represent filling of the corner/edge sites and those in red the face sites. Adapted from Ji et al . copyright 2007 with permission from Elsevier.…”
Section: Discussionsupporting
confidence: 87%
“… Left side and center: Schematic illustration of the five or three different H‐binding sites (below the red horizontal line) that have been identified previously and how they correlate to large and medium particles . The notation 6/3,4 indicates that the H atom in site 6 exists ontop of or in the presence of sites 3 and 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all of these studies, unprecedented new details on the coverage and binding sites of adsorbates in situ or operando have been revealed. Further, similar XAS studies in gas-phase catalytic reactors have been reported, including H on supported Pt clusters in zeolites and various flat supports [101] as well as ethylene on Pt and its different molecular geometries (atop p-bonded, bridged di-s bonded, and a dehydrogenated vertical ethylidyne species) as the temperature was increased, revealing the ability of the Dm technique to differentiate between different bonding geometries [102] on Pt, and even ethylene-type intermediates in the hydroepoxidation of propene over Au [103]. With the complexity of the systems and reactions that can be studied with the Dm technique increasing more recently, biofuel cell investigations and biocatalysis experiments could come into focus soon, with some experiments already underway [104].…”
Section: The Future Of Operando Xassupporting
confidence: 75%